How do employees' perceptions about the effectiveness of human capital management (HCM) affect the performance of subnational governments in Colombia? (2016)
Even though the literature has identified human capital management (HCM) as one of the key components of any public organization?s management (Koch & McGrath 1996; Bowen & 2004; O'Toole & Meier, 2009; Walker & Andrews, 2015), literature regarding Latin America is scant. This work aims to explore the relationship between HCM and subnational governments' performance in a Latin American country. We rely on survey data to build an index of four key areas of HCM (workforce planning, employment management, performance management and organizational climate management). Furthermore, the performance of subnational governments was measured through performance indices created by the National Planning Department (NPD), the Ministry of Finance and Ministry of HeaIth. By means of structural equation modeling (SEM), we find a statistically significant negative relationship between employment management and the performance of subnational governments